Upaya Mengurangi Perilaku Agresif melalui Konseling Kelompok Naratif bagi Siswa Kelas VII SMP Negeri 1 Luwuk - Lambause*, Hasan; Lambause, Awaldin; Lisabe, Chandra M; Yusuf, Moh. Amin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to examine efforts to reduce aggressive behavior in seventh grade students of SMP Negeri 1 Luwuk through group counseling using a narrative approach with externalization and reauthoring techniques. This research is a counseling guidance action research (PTBK) and is carried out in two cycles. In this study, the data collection method used observation, interviews, and psychological scale questionnaires. The data analysis technique used in this research is quantitative and qualitative data analysis. The results showed that the level of student aggressive behavior decreased after the narrative group counseling service. There is a decrease of 16.53% after narrative group counseling for 2 cycles